#### Answer

$k=\dfrac{6r-bt}{a}$

#### Work Step by Step

Using the properties of equality, in terms of $
k
,$ the given equation, $
ak+bt=6r
,$ is equivalent to
\begin{array}{l}\require{cancel}
ak=6r-bt
\\\\
k=\dfrac{6r-bt}{a}
.\end{array}

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$k=\dfrac{6r-bt}{a}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.